MiR-502 is the first reported miRNA simultaneously targeting two components of the classical non-homologous end joining (C-NHEJ) in pancreatic cell lines. Issue 1 (January 2020) - Smolinska, Agnieszka; Swoboda, Julia; Fendler, Wojciech; Lerch, Markus M.; Sendler, Matthias; Moskwa, Patryk
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the deadliest cancers. Acquired inherited and/or somatic mutations drive its development. In order to prevent the formation of these mutations, precise and immediate repair of any DNA damage is indispensable. Non-homologous end-joining (NHEJ) is the key mechanism of DNA double-strand break repair. Here, we report that miR-502 targets two components in pancreatic cell lines, Ku70 and XLF of the C-NHEJ. Interestingly, we also observed an attenuated cell cycle response to gamma ionizing radiation (γ-IR) via diminished phosphorylation of checkpoint kinase 1 (Chk1) on serine 345 in these cell lines. Altogether, pancreatic cells showed increased susceptibility to γ-IR via direct inhibition of DNA double-strand break repair and attenuation of the cell cycle response. Abstract : Cell culture; Cell death; DNA repair; Gene mutation; Chemotherapy; miRNA; DSB; NHEJ; PDAC; DNA repair.